2011
DOI: 10.1289/ehp.1002613
|View full text |Cite
|
Sign up to set email alerts
|

Time-Series Analysis of Mortality Effects of Fine Particulate Matter Components in Detroit and Seattle

Abstract: BackgroundRecent toxicological and epidemiological studies have shown associations between particulate matter (PM) and adverse health effects, but which PM components are most influential is less well known.ObjectivesIn this study, we used time-series analyses to determine the associations between daily fine PM [PM ≤ 2.5 μm in aerodynamic diameter (PM2.5)] concentrations and daily mortality in two U.S. cities—Seattle, Washington, and Detroit, Michigan.MethodsWe obtained daily PM2.5 filters for the years of 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(115 citation statements)
references
References 40 publications
10
103
0
2
Order By: Relevance
“…The percent contribution of elemental carbon is also higher in urban areas of Japan than in the United States; therefore, it is possible that the difference in the results of our study could have arisen from the difference in the mixture of chemical composition. Although a few recent studies focused on the effect of short-term exposure to certain PM compositions on mortality [26][27][28] , the results were inconsistent. Further studies are needed to examine which component is more influential.…”
Section: Discussionmentioning
confidence: 99%
“…The percent contribution of elemental carbon is also higher in urban areas of Japan than in the United States; therefore, it is possible that the difference in the results of our study could have arisen from the difference in the mixture of chemical composition. Although a few recent studies focused on the effect of short-term exposure to certain PM compositions on mortality [26][27][28] , the results were inconsistent. Further studies are needed to examine which component is more influential.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies A few panel and population studies published during or after 2009 have included transition metals (Bell et al, 2009a;de Hartog et al, 2009;Ito et al, 2011;Mostofsky et al, 2012;Ostro et al, 2009Ostro et al, , 2010Suh et al, 2011;Zhou et al, 2011). A comparison of the relative harmfulness of different metals is not possible at this point, because most of the studies have included only a few transition metals, most often zinc or nickel, and there is substantial variability in the outcomes available.…”
Section: Transition Metals and Metal Compoundsmentioning
confidence: 99%
“…The United Kingdom Expert Panel on Air Quality Standards (EPAQS, 2009) used an exposure-response model from Seilkop & Oller (2003) and Norwegian studies by Grimsrud et al (2002Grimsrud et al ( , 2003 After the above-mentioned paper by Lippmann et al (2006), several reports followed up on the contribution of nickel to the adverse effects on health of fine PM and found some support for the hypothesis that fuel combustion in power generation (which usually emits nickel and vanadium) could contribute to the risk of cardiovascular disease (Bell et al, 2009b;Zhou et al, 2011;Suh et al, 2011). The strongest indication is from a recent case-crossover study on stroke by Mostofsky et al (2012), who found nickel to be the element that showed the strongest (although non-significant) association with stroke incidence, surpassed only by black carbon.…”
Section: Later Reviews and Recent Original Papersmentioning
confidence: 99%
“…Atmospheric O 3 also contributes to global climate change because of its absorption of the infrared radiation, constituting one of the important short-lived climate pollutants. Additionally, high levels of surface O 3 exert deleterious impacts on ecosystems and human health Zhou et al, 2011) and O 3 is one of the criteria pollutants regulated by the environmental agencies in many countries, including the US Environmental Protection Agency (US EPA) and China's Ministry of Environmental Protection (China MEP).…”
Section: Introductionmentioning
confidence: 99%